2022
DOI: 10.21037/tlcr-22-350
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of the efficacy and safety of immune checkpoint inhibitors plus anlotinib versus immune checkpoint inhibitors alone as the treatment of advanced non-small cell lung cancer in the real world

Abstract: Background: Anlotinib is a new multi-target tyrosine kinase inhibitor (TKI) and has been shown to have antitumor effects and synergistic antitumor effects with immunotherapy only in animal studies and in the 2nd-line treatment in small clinical trials. A real-world study with large sample to compare the efficacy and safety of anlotinib plus immune checkpoint inhibitors (ICIs) with ICIs alone in the multiline treatment of advanced non-small cell lung cancer (NSCLC) was urgently needed. Methods: The data of 535 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The included studies[ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] in this analysis were conducted between January 2017 and September 2022 [ Table 1 ]. Of the 1720 studies, 17 met the inclusion and exclusion criteria, comprising 5 randomized controlled trials[ 21 , 25 , 34 , 35 , 36 ] and 12 retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The included studies[ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] in this analysis were conducted between January 2017 and September 2022 [ Table 1 ]. Of the 1720 studies, 17 met the inclusion and exclusion criteria, comprising 5 randomized controlled trials[ 21 , 25 , 34 , 35 , 36 ] and 12 retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies[ 20 , 21 , 22 , 24 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 ] reported HR values of PFS between the PD-1/PD-L1 plus AAs and monotherapy in NSCLC patients. By heterogeneity test, I 2 = 75%, P < 0.00001, using the random-effect model (RE model), the results demonstrated a statistically significant prolongation of PFS in the PD-1/PD-L1 plus AAs group compared to the monotherapy group (HR = 0.61, 95% CI: 0.50–0.75, P < 0.00001), as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has validated that the anti-PD-1 ICIs can prevent the differentiation of osteoclast precursor cells to osteoclasts by intercepting CCL2 generation, which contributes to enhanced anti-tumor immunity [ 31 ]. Pre-existing evidence has confirmed the positive effect of TKIs plus ICIs for patients with solid tumors and metastases [ 32 , 33 , 34 ]. However, limited clinical investigations have focused on the efficacy and safety of immunotargeted therapy and BMAs for metastatic HCC patients with BoM.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of immune checkpoint inhibitors (ICIs) has represented a milestone in lung cancer treatment that significantly improves the overall response and survival of lung cancer patients. They were recommended to use in advanced stage lung cancer patients in combination with chemotherapy or targeted therapy ( 1 ). But in locally advanced and inoperable non-small cell lung cancer (NSCLC) patients, concurrent chemoradiotherapy (cCRT) was still standard therapy according to National Comprehensive Cancer Network (NCCN) guideline version 4, 2023 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%